Effectiveness of the Bern Ambulatory Interprofessional Rehabilitation (BAI-Reha) programme for patients with chronic musculoskeletal pain: a cohort study (Swiss Medical Weekly, 2017)
QUESTIONS UNDER STUDY Chronic pain has a high impact on individuals and society. (Cost-)effective interventions are desperately needed. We evaluated short- and long-term effects of the Bern Ambulatory Interprofessional Rehabilitation (BAI-Reha) for patients with chronic musculoskeletal pain. METHODS We analysed data prospectively collected from patients with chronic musculoskeletal pain before and after BAI-Reha (at 12 weeks, 1 year and 2 years) using linear mixed-models and logistic generalised estimating equations. RESULTS The first thirty consecutive patients with chronic musculoskeletal pain, aged between 20 and 73 years (mean 44.83, standard deviation 12.57 years) were included. We found significant changes over time compared with baseline for return to work (p